2012
DOI: 10.3748/wjg.v18.i11.1249
|View full text |Cite
|
Sign up to set email alerts
|

CCL7 and CCL21 overexpression in gastric cancer is associated with lymph node metastasis and poor prognosis

Abstract: These results suggest that overexpression of these two CC chemokine ligands is associated with tumor metastasis and serves as a prognostic factor in patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…Besides, CCL21 plays roles in the regulation of ERK pathway in human non-small cell lung cancer cells (26). CCL21 is downregulated in many cancers and associated with lymph node metastasis, poor prognosis (27), apoptosis (26), cell cycle (28) and tumor growth (29). SPARCL1 belongs to SPARC family that contains ten protein members (30).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, CCL21 plays roles in the regulation of ERK pathway in human non-small cell lung cancer cells (26). CCL21 is downregulated in many cancers and associated with lymph node metastasis, poor prognosis (27), apoptosis (26), cell cycle (28) and tumor growth (29). SPARCL1 belongs to SPARC family that contains ten protein members (30).…”
Section: Resultsmentioning
confidence: 99%
“…Adipose-derived CCL7 may also have an adverse effect in the stomach, as high gastric CCL7 levels in gastric cancer patients has been correlated with more advanced tumour progression. 50 Dysregulation of the gut microbiome by HFD and H felis infection may also have increased systemic inflammation and contributed to the adipose or gastric pathology observed in H felis/HFD mice. Mice on HFD show altered gut microbiome composition and increased endotoxemia compared with mice on control diet.…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al (56) reported that CCL7, which is induced by carcinoma-associated fibroblasts, significantly induced the ability of migration of oral squamous cells. Similarly, CCL7 was found to be positively correlated to invasion and metastasis and patient survival of gastric cancer (57). More recently, Rajaram et al (34) found that fibroblast-secreted CCL7 is capable of promoting proliferation of breast cancer cells.…”
Section: Breast Cancer Mmp1mentioning
confidence: 97%